STUDY EVOLUTION OF PLANETARY NEBULA HUBI 1 - Megawati, Sri
Stellar evolution is a description of the way a star changes over the course of time. Each star has different stages of evolution depending on its initial mass. Planetary nebulae are the final stages of evolution of low mass stars and intermediate mass stars, before the white dwarf stages. HuBi 1 is a double-shell planetary nebula because of its reverse ionization structure. This reverse ionization structure is caused by shock that forms when the central star of HuBi 1 (IRAS 17514-1555) throws material at high velocity at the time when it experiences born-again event which is triggered by very late thermal pulse. In this final project, we study the evolution of central star of planetary nebula HuBi 1 and its physical parameters. For modelling the evolution of the central star, we use MESA code. By using mass, metallicity, rotational speed, wind scheme, and alpha mixing length as input parameters of MESA, we get some output parameters to build stellar evolution track on H-R diagram. Stellar evolution models show that stars experience very late thermal pulse before born-again event, which is very rare in white dwarf star evolution.